Integrating soft skills in nursing clinical skill assessments for aseptic procedures: a clinical audit approach - Jamaludin, Thandar Soe @ Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aesah @ Naznin; Chan, Chong Mei; Noviani, Wulan (Semerak Ilmu Publishing, 2025)
Nursing academics play a crucial role in cultivating appropriate attitudes towards aseptic techniques among nursing students. It is imperative to raise awareness among students about their responsibility in preventing healthcare-associated infections to improve patient outcomes and quality of life, starting with teaching and assessing these principles during their education, ensuring a balance between technical proficiency and the essential soft skills inherent to nursing care. This study aimed to examine the soft skill elements in objectively structured clinical skill assessment on aseptic procedures in the undergraduate nursing programme. A clinical audit was carried out on the retrospective structured clinical skill assessment exam questions by using the clinical skill assessment index III (CSAI-III) instrument. A total of 51 aseptic procedures set of exam questions were collected from 7 higher learning institutions in Malaysia where they offered the undergraduate nursing programme. The data were analysed descriptively. There were 51 aseptic procedures out of 237 collected exam documents found and analysed in this study. The aseptic procedures were grouped into 11 types to make them more specific. Although there are nine soft skill elements were identified in relation to aseptic procedures, including communication, social and responsibility, critical thinking, problem-solving, teamwork, leadership, professional and ethical decision-making, numeracy, and interpersonal skills. However, communication skills were predominantly present in 80.4% of the OSCE documents analyzed, while other soft skill elements were notably absent from the assessment rubrics. Notably, all 51 aseptic procedure assessments provided necessary equipment, eliminating the need for students to gather items, though none specified allocated time for scenario review, and only 43.1% included clear instructions for students. Thus, the current aseptic procedure checklist of clinical skill assessment needs improvement, especially the soft skills components. Besides, higher-learning nursing institutions in Malaysia should visit and revise the content of their checklist and the related materials if they are concerned about quality graduates and ultimately improve the quality nursing care towards their patients.